Arthritis in Two Patients With Partial Recombination Activating Gene Deficiency - Wu, Kevin Y.; Purswani, Pooja; Ujhazi, Boglarka; Csomos, Krisztian; Snezhina, Mihailova; Elissaveta, Naumova; Stefanov, Stefan; Sharapova, Svetlana; Ellison, Maryssa; Milojevic, Diana; Savic, Sinisa; Sargur, Ravishankar; et al. (Frontiers in Pediatrics, 2019)
Autoimmunity is becoming an increasingly recognized complication in patients with primary immunodeficiencies (PIDs), including a variety of combined immune deficiencies such as Recombination Activating Gene (RAG) defects. The approach to treating autoimmunity in PID patients is complex, requiring a balance between immunosuppression and susceptibility to infection. Inflammatory arthritis is a feature of immune dysregulation in many PIDs, and the optimal treatment may differ from first line therapies that usually consist of disease-modifying anti rheumatic drugs (DMARDs). An example of mechanism-based therapy of arthritis in PID uses blockade of IL-6 signaling with tocilizumab for patients with STAT 3 gain-of-function (GOF) mutation and augmented IL-6 pathway. Herein, we describe two PID cases with arthritis who were found to have defects in RAG. One patient with refractory inflammatory arthritis experienced remarkable improvement in symptoms with tocilizumab therapy. Arthritis can be a clinical feature of immune dysregulation in RAG deficiency, and tocilizumab therapy has been suggested to have utility in treatment of arthritis in RAG deficiency.